Context-aware Automatic Haptic Effect Generation Algorithm for Improved Content Viewing Experiences - Li, Yaxuan; Yoo, Yongjae; Weill-Duflos, Antoine; Cooperstock, Jeremy R. (2021 IEEE World Haptics Conference (WHC), 2021)
We propose an automatic vibrotactile content creation pipeline considering contextual information based on the movie's audiovisual content for improving the overall hapto-audio-visual (HAV) experience. The algorithm extracts significant features from video files and generates the haptic stimuli corresponding to the video content. We implement the algorithm on a low-cost system with nine actuators attached to the chair and will evaluate the system performance with 20 participants using six movie clips in the future.